Thucydides and the ancient simplicity : the limits of political realism - Crane, Gregory, 1957- (University of California Press, 1998)
Famous both as an analysis of power politics and as a classic of political realism, Thucydides' History of the Peloponnesian War is the earliest surviving realist text in the European tradition. From the opening speeches, Thucydides' Athenians emerge as a new and frightening source of power, oblivious to the rules and shared values under which the Greeks had operated for centuries. Gregory Crane shows how many of the assumptions that Thucydides attributed to his actors - and that seem commonplace to us today - boldly critique the operative assumptions of the archaic Greek elites. Crane's sophisticated claim for the continuing usefulness of the political examples of the classical past will appeal not only to classicists but to political scientists and anyone interested in the conflict between the exercise of political power and the preservation of human freedom and dignity.